2021
DOI: 10.1002/pmic.202000305
|View full text |Cite
|
Sign up to set email alerts
|

In‐depth proteomic analysis of Plasmodium berghei sporozoites using trapped ion mobility spectrometry with parallel accumulation‐serial fragmentation

Abstract: Sporozoites of the malaria parasite Plasmodium are transmitted by mosquitoes and infect the liver for an initial and obligatory round of replication, before exponential multiplication in the blood and onset of the disease. Sporozoites and liver stages provide attractive targets for malaria vaccines and prophylactic drugs. In this context, defining the parasite proteome is important to explore the parasite biology and to identify potential targets for antimalarial strategies. Previous studies have determined th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 30 publications
(55 reference statements)
1
40
0
Order By: Relevance
“…Also, the combination of trapped ion mobility spectrometry (tims) and Parallel Accumulation Serial Fragmentation (PASEF) effectively allows to maximize both throughput and sensitivity. This new technology has recently been used for analysis of complex samples in different research fields, such as the exploration of the proteome in human cerebrospinal fluid (Macron et al, 2020), detection of antibacterial peptides in the human endometrial fluid (Azkargorta et al, 2020) or the proteome of the malaria parasite Plasmodium (Hamada et al, 2021). To our knowledge, this is the first study where timsTOF is applied for neuropeptide and sORF discovery and only the second top-down MS study where non-digested peptide samples are identified using a timsTOF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the combination of trapped ion mobility spectrometry (tims) and Parallel Accumulation Serial Fragmentation (PASEF) effectively allows to maximize both throughput and sensitivity. This new technology has recently been used for analysis of complex samples in different research fields, such as the exploration of the proteome in human cerebrospinal fluid (Macron et al, 2020), detection of antibacterial peptides in the human endometrial fluid (Azkargorta et al, 2020) or the proteome of the malaria parasite Plasmodium (Hamada et al, 2021). To our knowledge, this is the first study where timsTOF is applied for neuropeptide and sORF discovery and only the second top-down MS study where non-digested peptide samples are identified using a timsTOF.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we introduce a two-step methodology combining firstly a trapped ion mobility spectrometry coupled to a time-of-flight mass analyzer (timsTOF) to generate the highest quality MSMS spectra, secondly the MS 2 ReScore (Silva et al, 2019) application leading to an improved identification of potential bioactive peptides in different regions of the mouse brain. timsTOF offers an enhanced peptide coverage and reduction in chemical noise (Lubeck et al, 2018) because of its extra dimension of separation (Meier et al, 2018), previously described in different applications in the field of clinical proteomics (Azkargorta et al, 2020;Macron et al, 2020;Hamada et al, 2021;Liu et al, 2021). The MS 2 ReScore tool, including MS 2 PIP that predicts the fragment ion intensity as an additional feature, DeepLC predicting retention times (Bouwmeester et al, 2021) and the post-processing tool Percolator, further boost the yield of identified peptides.…”
Section: Introductionmentioning
confidence: 99%
“…For DIA-MS, further innovations in instrumentation and informatics will be key to pushing the boundaries of improved sensitivity and throughput. [73][74][75][76]…”
Section: Mass Spectrometrymentioning
confidence: 99%
“…In order to define the repertoire of 6-cys proteins expressed at the sporozoite stage, we first analysed the proteome datasets of P. falciparum 22,26 , P. vivax 24 , P. yoelii 26 and P. berghei 21 sporozoites. As expected, P36 and P52 were identified by mass spectrometry in sporozoites from all four species.…”
Section: Analysis Of the Repertoire Of Plasmodium Sporozoite 6-cys Proteins Suggests That P36 P52 And B9 Are Employed By Infectious Sporomentioning
confidence: 99%
“…Plasmodium 6-cys proteins are typically expressed in a stage-specific manner, and have been implicated in protein-protein interactions in P. falciparum merozoites 16,17 , gametocytes 18,19 , ookinetes 20 and sporozoites 11 . Proteomic studies have shown that, in addition to P36 and P52, Plasmodium sporozoites express three 5 other 6-cys proteins, P12p, P38 and B9 [21][22][23][24] . While the contribution of P12p and P38 had not been studied until now, a previous study reported that the protein B9 is not expressed in sporozoites due to translational repression, and is not required for sporozoite invasion but is needed during infection of hepatocytes for early maintenance of the PV 15 .…”
Section: Introductionmentioning
confidence: 99%